The effect of caffeine on some indicators of bone metabolism in rats - Abdelkarem, Hala Mohamed Mokhtar; Al-Badr, Nawal Abudall; Al-Naser, Hanan Seleim (European Journal of Chemistry, 2014)
The propose of this article is to evaluate the effect of caffeine on some indicators of bone metabolism in rats by biochemical measurement of minerals, bone densitometry and histometry. Forty eight Wistar albino male rats, age 6-8 weeks and weighing 100±0.11 g were randomly divided into four groups (12 rats each). Each group of animals received balanced diet; the second, third and fourth groups received pure caffeine dissolved in distilled water with different oral doses (0.35, 0.43 and 50 mg/day) for 12 constitutive weeks. Blood samples were withdrawn at 3, 6, 9 and 12 weeks. Serum and urinary calcium, phosphorus, magnesium and caffeine were estimated. Bone density and bone length were measured. Bone minerals were also estimated. The data revealed that the bone density was significantly decreased (p ≤ 0.05) in the fourth set (1.05±0.10 g/cm3) for right femur rats. The length of right femur increased with more doses of caffeine and it was highly significant in the fourth group (3.40±0.12cm). The proportion of each calcium, phosphors and magnesium in bone ash was significantly lower (p ≤ 0.05). Serum levels of calcium, phosphors and magnesium were decreased with increasing the dose over time. The levels of urinary calcium and magnesium were increased significantly (p ≤ 0.05) in group 4, but phosphors was raised (p ≤ 0.05) in all groups. In conclusion, intakes of caffeine in amounts >300 mg/dl significantly affected the quantitative composition of the bone and this finding lead to be at a greater risk for bone loss. These results suggested that appropriate lifestyle changes to conserve bone mineral density (BMD) by reducing the consumption of caffeine and need further studies to elucidate the mechanism that caffeine effects on bone metabolism.